2003
DOI: 10.31729/jnma.1673
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Profile of Patients Attending Neuropsychiatric Opd at the Western Regional Hospital, Pokhara

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our finding is in accordance to Shrestha MR et al who observed that 32.3% patients were in the age group of 21-30 years.1 Our finding can further be supported by Fahmida A et al who observed that 42% patients were between 18 to 27 years and 35% were between 28 to 37 years. 2 Similar findings were also observed by other studies 6,7,8,9,10,11,12.…”
supporting
confidence: 85%
“…Our finding is in accordance to Shrestha MR et al who observed that 32.3% patients were in the age group of 21-30 years.1 Our finding can further be supported by Fahmida A et al who observed that 42% patients were between 18 to 27 years and 35% were between 28 to 37 years. 2 Similar findings were also observed by other studies 6,7,8,9,10,11,12.…”
supporting
confidence: 85%